Multifunctional Hydrogels Based on Cellulose and Modified Lignin for Advanced Wounds Management - Diana Elena Ciolacu; Raluca Nicu; Dana Mihaela Suflet; Daniela Rusu; Raluca Nicoleta Darie-Nita; Natalia Simionescu; Georgeta Cazacu; Florin Ciolacu (MDPI AG, 2023)
Considering the complex process of wound healing, it is expected that an optimal wound dressing should be able to overcome the multiple obstacles that can be encountered in the wound healing process. An ideal dressing should be biocompatible, biodegradable and able to maintain moisture, as well as allow the removal of exudate, have antibacterial properties, protect the wound from pathogens and promote wound healing. Starting from this desideratum, we intended to design a multifunctional hydrogel that would present good biocompatibility, the ability to provide a favorable environment for wound healing, antibacterial properties, and also, the capacity to release drugs in a controlled manner. In the preparation of hydrogels, two natural polymers were used, cellulose (C) and chemically modified lignin (LE), which were chemically cross-linked in the presence of epichlorohydrin. The structural and morphological characterization of CLE hydrogels was performed by ATR-FTIR spectroscopy and scanning electron microscopy (SEM), respectively. In addition, the degree of swelling of CLE hydrogels, the incorporation/release kinetics of procaine hydrochloride (PrHy), and their cytotoxicity and antibacterial properties were investigated. The rheological characterization, mechanical properties and mucoadhesion assessment completed the study of CLE hydrogels. The obtained results show that CLE hydrogels have an increased degree of swelling compared to cellulose-based hydrogel, a better capacity to encapsulate PrHy and to control the release of the drug, as well as antibacterial properties and improved mucoadhesion. All these characteristics highlight that the addition of LE to the cellulose matrix has a positive impact on the properties of CLE hydrogels, confirming that these hydrogels can be considered as potential candidates for applications as oral wound dressings.